PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR : DENGAN VARIABEL INTERVENING KOMITMEN ORGANISASIONAL - -, Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2008)
ABSTRACT The objective of the research is to examine the direct effect of transformational leadership to organizational commitment, transformational leadership to organizational citizenship behavior, and organizational commitment to organizational citizenship behavior and also test the indirect effect of transformational leadership to organizational citizenship behavior with the mediating effect of organizational commitment. Sample are 42 lecturers from all faculties in area of Universitas Slamet Riyadi Surakarta (completely filled questionnaire). The samples we taken by Cluster Proportional Random Sampling technique. To test the hypothesis, the researcher uses the path analysis, meanwhile to process the data, the SPSS Release 10 program is used. Result of examination of the direct effect, shows that (1) there is direct effect between of the transformational leadership to organizational commitment, (2) there is direct effect between of the transformational leadership to organizational citizenship behavior, (3) there is direct effect between of the organizational commitment to organizational citizenship behavior and also (4) There is indirect effect between of the transformational leadership to organizational citizenship behavior through organizational commitment. Â  Keywords: transformational leadership, organizational commitment, organizational citizenship behavior.